A spatially resolved single-cell landscape of colorectal cancer liver metastasis reveals a stromal-tumor glycolytic signaling interaction - Chen, Jiahui; Wang, Zukai; Zhu, Bingwang; Guan, Guoxian (Frontiers in Cell and Developmental Biology, 2025)
BackgroundColorectal cancer (CRC) remains a leading cause of cancer mortality, with liver metastasis being the principal determinant of poor prognosis, but the spatial mechanisms orchestrating metastatic niches remain elusive.MethodTo dissect the molecular and spatial dynamics of CRC progression, we constructed an integrative atlas using 35 single-cell RNA-seq datasets and spatial transcriptomics from primary tumors, liver metastases, and matched normal tissues. Malignant epithelial subpopulations were stratified via inferCNV and CytoTRACE analyses. Stromal-tumor interactions were dissected using CellChat and NicheNet, with functional validation through in vitro co-culture and immunohistochemistry.ResultWe identified a transcriptionally distinct epithelial subpopulation, termed high-malignancy CRC (High-M CRC), enriched in metastatic lesions and characterized by enhanced stemness, MYC-driven transcriptional activity, and glycolytic reprogramming. Stromal-tumor interaction analyses revealed that cancer-associated fibroblasts (CAFs), particularly matrix CAFs (mCAFs), promote malignant progression via the HGF-MET-MYC signaling axis. Spatial transcriptomic mapping confirmed the physical proximity and molecular co-localization of High-M CRC cells and mCAFs, along with enriched glycolysis and MYC expression at the cell-cell interface. In vitro functional validation demonstrated that CAF-derived HGF activates MET-MYC signaling in CRC cells, enhancing their invasion and proliferation—effects reversible by MET knockdown.ConclusionWe unveil a spatially organized metabolic niche driven by stromal-tumor HGF-MET-MYC signaling. These findings offer novel insights into the stromal-tumor interaction and suggest actionable targets for therapeutic intervention in CRC.